2002
DOI: 10.1152/ajpregu.00732.2001
|View full text |Cite
|
Sign up to set email alerts
|

Natriuresis induced by mild hypernatremia in humans

Abstract: The hypothesis that increases in plasma sodium induce natriuresis independently of changes in body fluid volume was tested in six slightly dehydrated seated subjects on controlled sodium intake (150 mmol/day). NaCl (3.85 mmol/kg) was infused intravenously over 90 min as isotonic (Iso) or as hypertonic saline (Hyper, 855 mmol/l). After Hyper, plasma sodium increased by 3% (142.0 +/- 0.6 to 146.2 +/- 0.5 mmol/l). During Iso a small decrease occurred (142.3 +/- 0.6 to 140.3 +/- 0.7 mmol/l). Iso increased estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 45 publications
8
63
1
Order By: Relevance
“…However, interventional studies in healthy humans with acute salt loading or longer lasting salt diets do not corroborate this hypothesis. Thus, slow salt loading by an infusion of saline markedly suppressed PRA without any detectable changes in the arterial blood pressure [82] or even a slight decrease in blood pressure in humans [2]. Similarly, PRC was reduced by a saline infusion in dogs without any detectable changes in MABP [9].…”
Section: Regulation Of the Renin System By Salt-dependent Changes In mentioning
confidence: 89%
“…However, interventional studies in healthy humans with acute salt loading or longer lasting salt diets do not corroborate this hypothesis. Thus, slow salt loading by an infusion of saline markedly suppressed PRA without any detectable changes in the arterial blood pressure [82] or even a slight decrease in blood pressure in humans [2]. Similarly, PRC was reduced by a saline infusion in dogs without any detectable changes in MABP [9].…”
Section: Regulation Of the Renin System By Salt-dependent Changes In mentioning
confidence: 89%
“…However, there is evidence of blood pressure-independent natriuresis and regulation of the renin system (21-24, 353, 746, 747). It has been found that acute salt loading, either by isotonic or hypertonic solutions, was followed by natriuresis without changes in blood pressure, and in one study, this effect even occurred together with a fall in blood pressure (22). These findings suggest that the response to sodium load may take place in the absence of increases in blood pressure, and therefore, the pressure-natriuresis concept may be inadequate (75).…”
Section: B Salt Intakementioning
confidence: 95%
“…This response, termed dehydration natriuresis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), plays an important role in preventing further accentuation of hypernatremia and the accompanying rise in extracellular tonicity. A similar natriuresis is seen following infusion of hypertonic saline (12).…”
Section: Introductionmentioning
confidence: 99%